The development of quality control system providing road-building services - Sadova, Mariia (Skhid, 2015)
Determined that the effectiveness of the management of enterprise road construction, largely determined by the quality of road works. Over the past 15 years in the industry made a lot of work to improve quality control system, which was due to a change in the economic model of the national economy. A great amount of work on a mechanism of quality control, based on compliance with existing regulations and design documentation. This could substantially improve the quality of road works to reduce the number of deviations from the requirements. However, if you switch from road works quality indicators to the indicators of the state of the road network, it must be noted that the volume of outstanding problems in recent years is growing. An approach to the development of a comprehensive quality control system of road-construction services, based on the model of the formation of the relationship of constructive, technological and organizational parameters of road works, which analyzes the control parameters listed in the production stage and assess their impact on the quality and reliability of road construction at an appropriate stage operation, which enables integrated control: the quality of the individual types of road works; materials used in road construction; preparation and adoption of constructive-technological and organizational decisions during the road construction.